PENGELOLAAN PEMBELAJARAN NILAI-NILAI AGAMA ISLAM PADA PENDIDIKAN ANAK USIA DINI (PAUD) "AISYIYAH KREATIF DI KOTA MAGELANG - Kusmitaningsih , Wiwik (2011)
The purpose of the research is to obtain a clear point of view about the learning management of Islamic values education at Early Childhood Education of "Aisyiyah Kreatif in Magelang, which consists of the characteristics of RPP, characteristics of methods and characteristics of teacher-pupil relationship. The place of the research is in PAUD "Aisyiyah Kreatif in Magelang. The data analysis technique used is an interactive qualitative research that is a case study. Case studies are generally descriptive approaches revealing something as it is, how the learning management of Islamic values in Early Childhood Education (PAUD) "Aisyiyah Kreatif in Magelang is, and the factors that inhibit and encourage it, In order to collect the research data, the researcher conducted a direct contact (face to face) with the respondents in order to observe the behavior, opinions and attitudes based on the views of research subjects. The result of the research shows that learning Islamic values is understood and developed from the teaching the fundamental values embodied in the Quran and Hadist. Therefore, teaching Islamic values has certain characteristics, namely basic characteristics, characteristics of process, and characteristics of goal. Islamic value learning in early childhood is an early stage of introduction and cultivation of moral values and the foundations of Islamic order so that in its development has a major personality on the basis of Islamic values. Islamic value learning in early childhood includes aqidah (faith), ibadah (worship) and akhlak (moral), akhlak to God, human beings and environment, The learning menu is based on the Developmentally Appropriate Practice (development in accordance with the age and development of the children). It is developed through topics which are arranged gradually and systematically. The method of teaching Islamic values to young children is the eclectic methods of modeling, habituating, demonstrating and playing, story telling, and singing. The teachers of young children are also parents, colleagues, and pleasing friends to them. To optimize the teaching, harmonious relationship between the teachers and the pupils should be created. The teachers and the pupils together take part in the active learning activities, in physic, process, and environment aspects. The prominent characteristics of active learning are charming, interesting, pleasing, and beautiful.